Kain Sebagai Pasĕk-Pasĕk dalam Upacara Penetapan Sῑma Masa Mpu Siṇḍok: Korelasi Jenis Kain dan Kedudukan Penerimanya - Anisa, Siti Nur (Department of Archaeology, Faculty of Cultural Sciences, Universitas Gadjah Mada, 2024)
The type and quantity item as pasĕk-pasĕk received in the sīma establishing ceremony is different each receiver. This diversity is determined by the recipient’s position. Cloth and money are commonly used as pasĕk-pasĕk. A person’s social status can be known based on the type of cloth they wear. This research aims to mapping the distribution of cloth as pasĕk-pasĕk, reconstructing the correlation between individual position and the types of cloth received in the sīma ceremony, and reconstructing the ranking of cloth based the exclusivity of its ownership. The study uses inductive reasoning. The observation is focused on the type of wḍihan cloth mentioned in Mpu Siṇḍok’s inscription and position of the individual recipients. This study shows that each type of cloth has its own distribution scope related to the hierarchy of government official: central level, watak and wanua. Wḍihan gañjar haji and wḍihan bwat kliṅ are the type of cloth with the highest social value because they are only intended for Śrῑ Mahārāja. === Jenis serta jumlah barang sebagai pasĕk-pasĕk yang diterima dalam upacara sīma berbeda tiap penerimanya. Keberagaman tersebut ditentukan berdasarkan kedudukan penerima. Kain dan uang umum dijadikan sebagai pasĕk-pasĕk. Status sosial seseorang dapat diketahui berdasarkan jenis kain yang dipakainya. Penelitian ini bertujuan memetakan distribusi kain sebagai pasĕk-pasĕk, rekonstruksi korelasi jabatan individu dan jenis kain yang diterimanya dalam upacara sīma, serta membuat rekonstruksi pemeringkatan kain berdasarkan eksklusifitas kepemilikannya. Penelitian menggunakan penalaran induktif. Pengamatan difokuskan pada penyebutan jenis kain wḍihan dan jabatan dari individu penerimanya yang disebutkan dalam prasasti masa pemerintahan Mpu Siṇḍok. Penelitian ini menunjukkan hasil bahwa tiap-tiap jenis kain memiliki ruang lingkup distribusi tersendiri terkait dengan penjenjangan pejabat pemerintahan: tingkat pusat, watak, dan wanua. Kain jenis wḍihan gañjar haji dan wḍihan bwat kliṅ merupakan kain dengan nilai sosial tertinggi sebab hanya diperuntukan bagi Śrῑ Mahārāja.